Reinterpreting Qiwamah in Muhammad Abduh’s Thought: Implications for Women’s Emancipation and Domestic Violence Prevention in Indonesia - Jamiliya Susantin; Fadil Sj; Isroqunnah Isroqunnah (At-Tafkir, 2025)
This article examines the relevance of Muhammad Abduh's thoughts on women's emancipation for addressing Domestic Violence in Indonesia. The study addresses the ongoing issue of gender-biased religious interpretations that legitimize acts of violence within the household, a problem evidenced by more than 10,000 reported cases in 2023. Abduh was chosen due to the significant influence of his reformist ideas—particularly his views on qiwamah—on the development of Islamic family law in Indonesia, largely through the intellectual networks of Al-Azhar University. The objectives of this research are twofold: first, to descriptively analyze Abduh’s concept of qiwamah as articulated in his principal works (Tafsir al-Manar and Risalat al-Tawhid); and second, to evaluate its normative and practical relevance in shaping an Islamic legal framework that opposes domestic violence in the Indonesian context. The study employs a contextual hermeneutic method, supported by comparative analysis between Abduh’s ideas and Indonesian domestic violence legislation. The findings reveal that Abduh offers three central arguments: qiwamah as a moral and protective responsibility rather than a justification for male dominance; the spiritual and ethical equality of men and women; and the necessity of legal reform grounded in the principle of maslahah. These ideas are found to be in harmony with the core values of Indonesia’s Law No. 23 of 2004 on the Elimination of Domestic Violence. The study concludes that Abduh’s reinterpretation provides a strong theological foundation for the prevention of domestic violence in Indonesia, although its practical application remains challenged by conservative interpretations and the ongoing need for contextual adaptation.